La santé en francophonie canadienne : vivre en situation minoritaire influence-t-il la santé ? - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène (Bulletin de l’association des médecins de langue française, 2009)
La littérature suggère l'hypothèse d'une santé différentielle des francophones en situation minoritaire au Canada. L'effet de minorité sur la santé perçue a été mesuré à l'aide des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) de 2001 et 2003. Une analyse de régression logistique multivariée séquentielle montre que les francophones minoritaires – hommes et femmes – sont plus enclins à déclarer une moins bonne santé que les anglophones majoritaires. Contrairement aux femmes, cette disparité chez les hommes demeure significative même lorsque nous ajustons pour certains grands déterminants de la santé. L'étude illustre que l'action des déterminants de santé peut être ainsi modulée par le rapport minoritaire/majoritaire. Les inégalités ainsi révélées appellent à une réflexion sur les politiques d'accès linguistique aux soins de santé.

Profil santé des communautés anglophones minoritaires au Québec [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H. et Gagnon-Arpin, I. (2009). Profil santé des communautés anglophones minoritaires au Québec [infographie]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF). Santé Canada. fs-code-orig: Bouchard-2009e

Health profile of English-speaking minority communities in Quebec [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

Profil santé des communautés francophones minoritaires au Canada [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
Contexte : Les communautés francophones vivant en situation minoritaire évaluées à 1 million de personnes (4,4% de la population canadienne) sont dispersées un peu partout au pays. Les plus fortes concentrations sont en Ontario (509 265) et au Nouveau Brunswick (239 400), alors qu'ailleurs, on peut compter de 63 000 francophones (Alberta) à moins de 500 francophones (Nunavut). Ces communautés présentent un profil diversifié : elles sont en général moins jeunes, moins scolarisées, ont de plus faibles revenus. Elles sont davantage concentrés dans des régions où l'économie est plus instable rendant ainsi plus difficile le développement et l'accès aux ressources sociales. L'objectif de cette affiche est de présenter une sélection d'indicateurs décrivant certains aspects des déterminants de la santé de la population francophone en situation linguistique minoritaire. Méthode : Les indicateurs de santé sont extraits d'une analyse secondaire de l'ESCC combinant les cycles 2001, 2003 et 2005. L'analyse se fonde sur un échantillon d'adultes de 25 ans et plus de 244 382 : 12 583 francophones ; 256 966 anglophones. Le profil montre les situations et les déterminants les plus défavorables comparant la communauté minoritaire à la majorité anglophone dans l'ensemble du Canada excluant le Québec. Résultats : Sur l'ensemble des indicateurs sélectionnés (variables sociodémographiques, santé perçue, présence de maladie, difficulté à accomplir une tâche, services de santé, styles de vie, le sentiment d'appartenance), les communautés francophones présentent un profil de santé plus défavorable que la majorité anglophone et ce de façon plus marquée dans certaines zones géographiques. Conclusion : Les résultats permettent de soutenir que le rapport minoritaire/majoritaire semble traduire une inégalité sociale et d'accès aux ressources qui, traversée par les autres déterminants sociaux de la santé (statut socioéconomique, éducation et littératie, immigration) contribue de facto aux disparités de santé. Ils montrent l'importance d'approfondir et de mieux comprendre l'ensemble des déterminants de la santé ainsi que les interactions entre les contextes, les milieux de vie locaux, l'impact des politiques et la santé.
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H. et Gagnon-Arpin, I. (2009). Profil santé des communautés francophones minoritaires au Canada [infographie]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF). Santé Canada. fs-code-orig: Bouchard-2009c

Health profile of French-speaking minority communities in Canada [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H., & Gagnon-Arpin, I. (2009). Health profile of French-speaking minority communities in Canada [infographic]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF). Santé Canada. fs-code-orig: Bouchard-2009d

La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé /Healthcare Policy, 2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H., Gilbert, A. et Dubois, L. (2009). La santé en situation linguistique minoritaire. Politiques de Santé, 4(4), 36-42. https://www.ncbi.nlm.nih.gov/pmc/Article de revue s/PMC2700700/pdf/policy-04-036.pdf fs-code-orig: Bouchard-2009a

Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie] - Gagnon-Arpin, Isabelle; Bouchard, Louise; Gaboury, Isabelle; Bourbonnais, V.; Chomienne, Marie-Hélène (2009)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Gaboury, I., Bourbonnais, V. et Chomienne, M.-H. (2009). Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF), Université d’Ottawa. fs-code-orig: Gagnon-Arpin-2009a

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Comparison of dietary intake between Francophones and Anglophones in Canada: Data from CCHS2.2 - Batal, Malek; Makvandi, Ewa; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective To compare the dietary intake and food choices between Francophone Canadians in a state of linguistic minority (outside of Quebec) and the English-speaking majority. Methods We used the 2004 Canadian Community Health Survey (CCHS) cycle 2.2 (general health and 24-hour dietary recalls) to describe dietary intake of Francophone Canadians (excluding Quebec) and compare them to the English-speaking majority. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. The mean differences in daily nutrient and food intake were assessed by t and chi-square tests. Results Differences in total energy and daily food intakes by language groups were not observed in the sample; however, significant differences in weekly consumption were found in different age and sex categories: lower fruits and vegetables consumption, and vitamins and macronutrients intakes for older Francophone men and higher intakes of energy and saturated fat from “unhealthy” foods for Francophone men 19–30 years of age. Based on the Acceptable Macronutrients Distribution Range (AMDR), approximately 50% of the sample exceeded their acceptable energy intake from saturated fats, and 80% were below their required intake of linoleic fatty acid. Conclusion We confirmed that belonging to Francophone minorities in Canada affects food choices and nutritional well-being of this population. The most vulnerable groups identified by our study were Francophone men in the youngest (19-30) and older (50 and over) age categories. The extent to which the cultural setting influences the diet and, in turn, the health of the minority population needs further examination.

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Comorbidités entre maladies chroniques et problèmes de santé mentale fréquents : différences entre francophones et anglophones - Grenier, Jean; Gosselin, Dominique; Greenman, Paul. Samuel; Chomienne, Marie-Hélène; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Psy-Cause, 2016)

Disparities in COVID-19 infection rates across linguistic groups in long-term care homes in Ontario, Canada - Batista, Ricardo; Fitzgerald, Michael; Reaume, Michael; Kendall, Claire E.; Bjerre, Lise M.; Mahdavi, Roshanak; Imsirovic, Haris; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Helene; Hsu, Amy; Bouchard, Louise; et al. (BMC Public Health, 2026)
Background The COVID-19 pandemic has had a disproportionate impact on residents of long-term care facilities or nursing homes, characterized by significantly higher infection and mortality rates than in the general population. Previous research has highlighted significant disparities in COVID-19 outcomes, particularly among ethnic minorities. This study examines the association between belonging to a minority language community and COVID-19 infection rates in LTCFs in Ontario, Canada, at both the individual and facility levels. Methods We conducted a population-based retrospective cohort study of 85,367 LTC home residents in Ontario between January 15, 2019, and March 30, 2020, which we followed until March 31, 2021, using data from the Continuing Care Reporting System. We defined resident language (obtained from routine assessments in nursing homes) as English (Anglophone), French (Francophone), or other (Allophone), and we calculated a weighted average of languages spoken by residents in each LTC facility to determine the linguistic environment of the LTC facility. We calculated incidence rates of COVID-19 for each linguistic group, and we fitted multilevel logistic regression models to assess the main factors influencing the risk of COVID-19 infection, to account for individual-level and facility-level linguistic factors. Results The overall incidence of COVID-19 was 14.8%. The incidence of COVID-19 was higher among Allophones (23.6%) compared to Anglophones (13.1%) and Francophones (12.2%). Allophones in English homes (22.5%) showed significantly higher incidence rates compared to Anglophones (13.1%) and Francophones (11.0%) in these same homes. After adjusting for sociodemographic and clinical characteristics, the risk of COVID-19 remained significantly higher for Allophones compared to Anglophones (aOR 1.14, 95% CI 1.05–1.22), while residents living in language-discordant nursing homes had a non-significantly higher risk of COVID-19 (aOR 1.07, 95% CI 0.99–1.14). Conclusions Over the first two waves of the COVID-19 pandemic, the risk of COVID-19 infection in nursing homes was highest among residents whose primary language was a language other than English or French. The results of our study show that COVID-19 disproportionately affected populations living in minority linguistic communities. These findings may help informing public health interventions aimed at addressing the language barriers in long-term care in Ontario, and across Canada.